2012
DOI: 10.1186/1479-5876-10-31
|View full text |Cite
|
Sign up to set email alerts
|

PDCD6 is an independent predictor of progression free survival in epithelial ovarian cancer

Abstract: BackgroundProgrammed cell death 6 (PDCD6) beside its known proapoptotic functions may be a player in survival pathways in cancer. The purpose of this study is to further explore the roles of PDCD6 in epithelial ovarian cancer.MethodsLentiviral vector with shRNA for PDCD6 was used to investigate the effects of PDCD6 knockdown on cell growth, cell cycle, apoptosis and motility in ovarian cancer cells. Two hundred twelve epithelial ovarian cancer tissues were analyzed for mRNA expression of PDCD6 using RT-PCR. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
5
26
0
Order By: Relevance
“…In the present study, RT-qPCR was used to detect the differential expression of PDCD6 in CH and the results indicated that PDCD6 was significantly increased in the hippocampus of rats with CH compared with the control group. These results were consistent with those of a previous study (27). The results also indicated a negative correlation between miR-124-3p and PDCD6.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, RT-qPCR was used to detect the differential expression of PDCD6 in CH and the results indicated that PDCD6 was significantly increased in the hippocampus of rats with CH compared with the control group. These results were consistent with those of a previous study (27). The results also indicated a negative correlation between miR-124-3p and PDCD6.…”
Section: Discussionsupporting
confidence: 83%
“…Aberrant expression of PDCD6 has been observed in various types of human cancer and may act as either an oncogene or a tumor suppressor. For instance, PDCD6 was recently reported to be a tumor suppressor and may be a potential therapeutic target in glioblastoma (25); reintroduction of PDCD6 significantly reverses the effects of miR-183 in enhanced cell cycle/proliferation and inhibits the apoptosis of leukemia cell lines (26); and PDCD6 was highly expressed in metastatic ovarian cancer and induced cell migration/invasion (27). In the present study, RT-qPCR was used to detect the differential expression of PDCD6 in CH and the results indicated that PDCD6 was significantly increased in the hippocampus of rats with CH compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that PDCD6 is an independent predictor of progression-free survival in patients with epithelial ovarian cancer (7). However, its effect on ovarian cancer apoptosis is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, genes contributing to disease susceptibility are not necessarily associated with treatment response, as shown previously in the case of the well established RA susceptibility locus mapping to PTPN22 [8]. Interestingly, another RA risk SNP of TRAF1/C5 , the rs3761847, was found to be associated with anti-TNF treatment response in a Southern European population [29]. The rs 6427528 CD84 SNP, which was reported recently that may serve as a useful biomarker for response to etanercept treatment in RA patients of European ancestry [30], will be also investigated in the Cretan population in an attempt to clarify its putative role in this cohort.…”
Section: Discussionmentioning
confidence: 89%